New discovering on internal correlation of nematode communities’ characteristics in the Co Chien estuary, Ben Tre province - Quang, Ngo Xuan; Chau Ngoc, Nguyen (Vietnam Journal of Science and Technology, 2015)
Insight on internal correlation of nematode communities’ characteristicswas first investigated along the Co Chien estuary in order to understand a linkamong their densities, composition, diversity, morphometric and biomass. Researchresults showed high value in the nematode densities and diversities in thisestuary. Nematodes had medium size, individual biomass is rather small buttotal biomass in the communities is quite high due to their densities. Thenematode size, shape and biomass have significant relationship with densitiesand feeding type structure in their communities along the Co Chien estuary.